TAT VR: a Virtual Reality Simulator for Military Shooting Training - Girardi, Romullo; Pereira Filho, Adinê Alves; Teodoro, Gabriel Pinheiro; Oliveira, Jauvane C De (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
Traditional military shooting training methods have high costs, logistics complexity, spatial-temporal constraints, and safety risk. VR-based simulation can help address these drawbacks while serving as a platform for supplementing current training approaches, providing more convenience, accessibility, and flexibility. This work aims at analyzing the application of virtual reality in the Brazilian Army’s pistol shooting training through the TAT VR simulator. This simulator was tested by a sample composed of five Army officers and one Navy officer with practical shooting experience. The results were compared with reference values obtained from related work. The data showed that TAT VR reached the reference values for the two evaluated parameters: sense of presence and effectiveness.